Comparing the Role of Project-Based Teaching Method vs. Place-Based Teaching Method on Motivation of Iranian EFL Learners - et. al., Zahra Rezaei Bandari, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There are Methods and approaches which can help learners to be motivated. Students should have inspiring learning experiences already in the schools. To meet the elevated requirements of education and motivation, several different learning methods have been developed. Project-based learning (PBL) is one of these methods. On the other hand in our global society children are increasingly disconnected from their local history and cultural traditions. So there is a great need for a revival in connection to our heritage which place based learning facilitate it. This study is going to investigate effect of project based education and place based education on motivation of Iranian EFL learners. The main objective of the current research is to compare the benefits of these approaches and survey their role on Iranian EFL learners’ motivation. Participants of the study were 60 learners in upper-intermediate level who gave a PET as the homogenization test. Next, 40 participants were selected with respect to their proficiency level. Then, the researcher divided them into two experimental groups; experimental 1. (E1: project based instruction) and experimental 2 (E2: place based instruction); each group included 20 participants. The first instrument was the PET (Preliminary English Test) that was used to determine the proficiency level of the participants in this study. The data was collected from pretest, posttest and the Motivated Strategies for Learning Questionnaire (MSLQ) test. The data obtained through the pretest and posttest were be analyzed using SPSS software, those Iranian upper-intermediate EFL learners who have been taught by project based instruction outperformed those learners who have been taught by place based instruction.